Sterilization procedures for CO2 incubators. Issue 4 (October 2018) - Knegendorf, Leonard; Brill, Holger; Steinmann, Joerg; Pahl, Steffen; Steinmann, Eike; Brill, Florian H.H.
Abstract : N/A: Cell culture methods are utilized ubiquitously in science and pharmaceutical and biotech industries. Sterility is one crucial factor for maintenance of cells and creation of valid data from experiments. As cells are usually cultured in CO2 incubators, those are one bottleneck in terms of sterility in a cell culture lab. This review gives an overview on the different sterilization procedures for CO2 incubators on the market with emphasize to considerations from a practical point of view. It compares sterilization by dry heat, steam, gas and ultraviolet radiation in terms of validity and practicability in accordance with international standards and regulations and transfers literature consensus about these methods to CO2 incubators. As conclusion, the authors give recommendations for a sterile working environment in line with good cell culture practice.